Microbial spoilage of potato top pies : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Science, Massey University, Palmerston North - Masters, Fiona (Massey University, 1986)
The microbial spoilage of Potato Top pies was investigated to try to provide a view of the events taking place during the spoilage process which renders these pies unsuitable for public consumption. Pies used in this study were obtained from a commercial pie manufacturer and were stored at 4°c, 25c and 37°c, and the effects of storage at these temperatures studied. During the examination biochemical techniques were used in conjunction with microbiological methods. Aspects gained from this study can be summarised as below: . Major flora of all pie component parts (meat filling, pastry surround, potato topping) of freshly cooked pies and of pies stored at the three temperatures consisted primarily of gram positive rods and cocci. The origins of these organisms could be traced directly back to various stages of manufacture. . Within 24-36 hours of storage at 25deg c and 37°c numbers of gram positive organisms could reach above 107/gram of pie component. . No obvious organoleptic spoilage took place. Lack of off odours (NH 3; H2S); the presence of amylase producing Bacillaceae; pH decreases in spoiled pies - suggested that the utilisation of low molecular weight compounds (such as glucose) resulted in saccharolytic spoilage of the pies. . Bacterial numbers in the pies stored at 4°c did not rise above 105/gram within 28 days of storage. . Isolated dominant bacterial species were identified as Bacillus, ,, Streptococcus, Staphylococcus and Micrococcus,with the Bacillus., species and Streptococcus species inhibiting the growth of the other organisms.
Keywords: Pastry; Food -- Microbiology; Food spoilage